Inhibitory Effect of Carbohydrate on Flowering in Lemna perpusilla. I. Interaction of Sucrose With Calcium and Phosphate Ions - Posner, Herbert B. (1969)
Flowering in Lemna perpusilla 6746 grown on tenth-strength Hutner's medium under short days was inhibited by 30 mM sucrose, glucose or fructose, but not by mannitol. The inhibition by sucrose does not appear to be due to sucrose-induced acidification of the medium during growth, or to trace metal contaminants of the sugar. Inhibition was partially prevented by raising either Ca(2+) or phosphate to levels used in half-strength medium. Possible mechanisms for these effects are discussed.